Factors Related to Stunting Incidence in Toddlers Aged 24-59 Months in the Working Area of Kambang Community Health Center, Pesisir Selatan District - Rani Ashari; Vaulinne Basyir; Afriwardi Afriwardi; Mayetti Mayetti; Yusrawati Yusrawati; Desmawati Desmawati (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Stunting is a major nutritional problem in Indonesia, even in the world particularly in developing countries. The purpose of the study was to find out the factors related to stunting in toddlers aged 24-59 months in the Pesisir Selatan District. This study is an analytical survey study with cross sectional design. This research will be conducted in the Kambang Health Center, Lengayang District, in July 2022-January 2023. The population in this study was all mothers who had toddlers aged 24-59 months who were in the Kambang Community Health Center working area in 2021 which numbered 1081 toddlers. Sample used in this study is 180 samples. The sampling technique used in this study is proportional stratified random sampling. Data collection tool using questionnaires. Analysis of the data in this study using Chi-Square test and use multiple logistical regression tests. The results showed that there was a significant relationship between the age of the mother during pregnancy (p-value = 0.040), there was a relationship between the nutritional status of the mother (p-value = 0.003), there was a relationship between parity (p-value=0.034), there is a relationship between psychosocial parenting (p-value = 0.000), there is a relationship between environmental sanitation (p-value=0.000), there is no significant relationship between low birth weight (p-value = 0.071), there is a significant relationship between birth length (p-value = 0.016). Environmental sanitation is the most dominant factor in causing stunting. Environmental sanitation has a 6,512 times chance of causing stunting in toddlers aged 24-59 months in the working area of the Kambang Community Health Center, Pesisir Selatan District. It is recommended for health workers to provide supplements or supplements for pregnant women and toddlers for nutritional improvement and to educate them on nutritional knowledge.Keywords: Stunting, Mother Factors, Child Factors